MENAVIGASI STRATEGI PEMASARAN DI ERA PASCA-COOKIE DENGAN PENDEKATAN (Systematic Literature Review): (Systematic Literature Review) - maratush; Zulfikar, Muhammad Vicky (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
The gradual elimination of third-party cookies driven by privacy regulations and browser policies has fundamentally reshaped digital marketing practices. This shift creates challenges for marketers to maintain personalization effectiveness while respecting consumer data privacy. This study aims to systematically review existing literature on marketing strategies in the post-cookie era using a Systematic Literature Review (SLR) approach. Relevant studies were identified through reputable academic databases using predefined inclusion and exclusion criteria. The findings reveal that first-party data strategies, contextual advertising, artificial intelligence-driven analytics, and trust-based consumer engagement emerge as dominant approaches in privacy-oriented marketing. This review contributes both theoretically and practically by synthesizing strategic directions for sustainable digital marketing in the post-cookie era.